2017
DOI: 10.1159/000458438
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Combined with Therapeutic Hypothermia Is Associated with Cardiovascular Instability and Neurotoxicity in a Piglet Model of Perinatal Asphyxia

Abstract: The selective α2-adrenoreceptor agonist dexmedetomidine has shown neuroprotective, analgesic, anti-inflammatory, and sympatholytic properties that may be beneficial in neonatal encephalopathy (NE). As therapeutic hypothermia is only partially effective, adjunct therapies are needed to optimize outcomes. The aim was to assess whether hypothermia + dexmedetomidine treatment augments neuroprotection compared to routine treatment (hypothermia + fentanyl sedation) in a piglet model of NE using magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 70 publications
1
16
0
1
Order By: Relevance
“…4 Preclinical studies of perinatal HI, using newborn pigs (similar gross anatomical features of human neonatal brain 5 ) have been used to investigate cerebral energetics and metabolism during and after HI and to develop neuroprotective therapeutic strategies. 1,[6][7][8][9][10] Phosphorous ( 31 P) and proton ( 1 H) magnetic resonance spectroscopy (MRS) are gold standard magnetic resonance (MR) techniques for assessing injury severity, as the decline in cerebral energy measured in this manner correlates strongly with neurodevelopmental outcome. 11,12 Studies have demonstrated that 31 P-MRS-measured inorganic phosphate/exchangeable phosphate pool (Pi/epp), phosphocreatine (PCr)/Pi, and total nucleotide triphosphate (NTP)/epp ∼1 to 2 h after HI correlate linearly with the decline in cerebral energetics leading to secondary energy failure.…”
Section: Introductionmentioning
confidence: 99%
“…4 Preclinical studies of perinatal HI, using newborn pigs (similar gross anatomical features of human neonatal brain 5 ) have been used to investigate cerebral energetics and metabolism during and after HI and to develop neuroprotective therapeutic strategies. 1,[6][7][8][9][10] Phosphorous ( 31 P) and proton ( 1 H) magnetic resonance spectroscopy (MRS) are gold standard magnetic resonance (MR) techniques for assessing injury severity, as the decline in cerebral energy measured in this manner correlates strongly with neurodevelopmental outcome. 11,12 Studies have demonstrated that 31 P-MRS-measured inorganic phosphate/exchangeable phosphate pool (Pi/epp), phosphocreatine (PCr)/Pi, and total nucleotide triphosphate (NTP)/epp ∼1 to 2 h after HI correlate linearly with the decline in cerebral energetics leading to secondary energy failure.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, signi icantly higher Pi and pH (both p < 0.01) were noticed in patients with CLI than healthy control ones. Ezzati et al assessed [20] the wholebrain (phosphorus-31 and regional proton MRS biomarkers) nucleotide triphosphate/exchangeable phosphate pool was similar (p = 0.73) over 48h in large White male piglets. Kamath, et al recommend [21] to all patients with a history of previous thyroid operation, who come with vague symptoms like fatigue, muscle aches to undergo estimation of serum calcium, phosphorus and parathyroid hormone (PTH) screened for delayed hypoparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Newborn piglets offer a large brain size, the presence of gyri and sulci, similar white/grey matter ratio, and developmental age at term similar to the human brain. Our laboratory [ 26 ] and other investigators [ 25 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] have used the newborn piglet model as it provides the advantage of real-time measurements of physiologic parameters such as arterial blood gases and continuous blood pressure monitoring, which allows titration of FiO 2 to achieve a precise and reproducible degree of hypoxia-ischemia [ 25 , 27 , 32 , 38 ].…”
Section: Discussionmentioning
confidence: 99%